A comparative analysis of drilling process parameters for small and large holes in jute reinforced polyester composites using Box-Behnken design - Mustafa, Zaleha; Idrus, Noriqman Hakimi; Sheikh Md Fadzullah, Siti Hajar; Thongkaew, Kunlapat; Ng, Linfeng; Abd Aziz, Abdul Rashid (Penerbit UTeM, 2025)
The present work evaluates how selected levels of the drilling parameters contribute to the delamination in drilling natural fibre-reinforced composites, specifically small and large holes. The jute/ unsaturated polyester composites were fabricated through a combination of vacuum bagging and hot compression moulding using 40 vol. % woven jute fabric. The primary effects and interactions on delamination due to feed rate (20 – 100 mm/min), spindle speed (500 – 1500rpm) and drill tool diameter (small bits of 4 – 8 mm and large bits of 20 – 30 mm) were organized using Response Surface Methodology (RSM) and Box Behnken design. The optimal drilling parameters for the smallest delamination factor at feed rate of 60.00 mm/min, spindle speed (1000.00 rpm) and drill diameter (6.00 mm). For the larger hole, the delamination factor is at the lowest when using a feed rate of 30.00 mm/min, spindle speed of 700.00rpm and drill diameter of 20.00 mm. The outcomes revealed that the feed rate and spindle speed are the most critical factors in the delamination of jute/ unsaturated polyester composite during the drilling process.